Courseware for learning basic tajweed - Nurul Erinawati, Mohd Mukhiri (2014)
The purpose of this project is to develop courseware for learning basic Tajweed. This courseware is hoped to help the users to learn and understand Tajweed properly. Tajweed has many complicated rules, hence learning it is not always easy and fun. So, in order to overcome this problem, So, in order to overcome this problem, an attractive application is the modules of this courseware comprise of two parts which are Learning and Exercise. Learning module consists of explanation and example of Tajweed rules while Exercise module consists of series of questions to test the understanding of users. This courseware will hopefully improve the effectiveness of Taj weed learning compared to learning using conventional method. ADDlE model was chosen in development of this courseware.